The Taxonomy of Opportunities to Learn (TxOTL): a tool for understanding the learning potential and substance of interactions in faculty (online) learning community meetings - Alexandra C. Lau; Makenna Martin; Adriana Corrales; Chandra Turpen; Fred Goldberg; Edward Price (SpringerOpen, 2021)
Abstract Background While many research-based instructional strategies in STEM have been developed, faculty need support in implementing and sustaining use of these strategies. A number of STEM faculty professional development programs aim to provide such pedagogical support, and it is necessary to understand the activity and learning process for faculty in these settings. In this paper, a taxonomy for describing the learning opportunities in faculty (online) learning community meetings is presented. Faculty learning communities, meeting either in-person or (increasingly) online, are a common form of professional development. They aim to develop the pedagogical and reflective skills of participants through regular meetings centered on conversations about teaching and learning. Results The tool presented in this paper, the Taxonomy of Opportunities to Learn (TxOTL), provides a structured approach to making sense of the dynamic interactions that occur during faculty learning community meetings. The origins and development of the TxOTL are described, followed by a detailed presentation of the constructs that make up the TxOTL: communicative approach used in a conversation, the concepts developed, and the meeting segment category. The TxOTL characterizes the learning opportunities presented by a faculty learning community conversation through describing the content of the conversation as well as how participants engage in the conversation. Examples of the tool in use are provided through an application to a faculty online learning community serving instructors of a physical science curriculum. A visual representation used to compactly display the results of applying the taxonomy to a meeting is detailed as well. These examples serve to illustrate the types of claims the TxOTL facilitates. Conclusions The TxOTL allows one to examine learning opportunities available to a faculty learning community group, analyze concept development present in their conversations, track change over time in a given group, and identify patterns between meeting segment categories and communicative approaches. It is useful for researchers as well as facilitators of these STEM faculty professional development groups. The taxonomy is most applicable to faculty (online) learning communities, with limited use for workshops and K-12 professional development contexts.